The Role of Micro, Small and Medium Enterprises (MSMEs) and Entrepreneurship in Reducing Poverty - Vivi Handayani Manalu; Gerry Morado Alfonsus Sirait; Yulia Arya Sasti (Outline Journal of Economic Studies, 2026)
Purpose: This study aimed to explore the role of Micro, Small, and Medium Enterprises (MSMEs) and entrepreneurship in reducing poverty by providing employment opportunities and supporting economic growth. Methods: The research employed a qualitative approach to analyze the contribution of MSMEs and entrepreneurial activities in job creation and poverty alleviation. Results: Findings from the Ministry of Cooperatives and MSMEs of Indonesia in 2020 showed that the MSME sector contributed approximately 97% of total non-agricultural employment in Indonesia. MSMEs and entrepreneurial ventures often serve as the primary source of employment in many countries because of their ability to adapt quickly to market changes and consumer needs compared to large companies. Conclusions: The development and support of MSMEs and entrepreneurship can significantly improve the economy and reduce poverty. The increasing number of small and medium enterprises provides job opportunities for people who may find it difficult to obtain employment in the formal sector. Originality/value: This study highlights the novelty of linking MSMEs’ growth directly to poverty reduction, showing how their role in job creation supports vulnerable groups beyond their conventional economic function.